One-year Outcome of Stenting for Long Coronary Lesions, a Prospective Clinical Trial - Samad Ghaffari; Mohammad Reza Hasanian; Leili Pourafkari (Journal of Cardiovascular and Thoracic Research, 2010)
Background: Percutaneous coronary intervention (PCI) for long coronary lesions is associated with poor angiographic and clinical outcome compared with focal lesions. Here we describe our experience in PCI of such lesions with bare (BMS) or drug eluting stents (DES). Methods: Between October 2008 and September 2009, One hundred patients with one significant coronary artery stenosis of longer than 20 mm were enrolled in this prospective study. Demographic, clinical and angiographic data were collected and the rate of ischemic events and major adverse cardiac events (MACE) were evaluated in a mean follow up period of about 11.3±3.2 months. Results: Mean age of participants was 58.08±8.97 years. Seventy two (72%) patients were male and the remainders were females. Majority of patients underwent DES implantation [25 (25%) BMS, 75 (75%) DES, P<0.001)].There was no difference in frequency of major risk factors distribution among DES or BMS groups. Mean diameter of implanted stent was 2.8±0.033mm in DES group and 2.9±0.35 in group with BMS (P=0.214). The mean length of implanted stent was 25.8±3.08mm in DES and 23.36±0.mm in BMS groups (P<0.001). In-stent restenosis rate was significantly higher in BMS group [6(24%) in BMS and 5(6.9%) in DES, P=0.02]. MACE were observed in 7(9.3%) of patients with DES and 7 (28%) of patients with BMS (P=0.04). Conclusion: In long coronary lesions implantation of DES was associated with lower MACE compared with BMS in one year follow up. Studies with longer term follow up are needed to further clarify this issue.